Influence of crop establishment and microbial inoculants on profitability and nutrient concentrations of summer greengram (Vigna radiata) - Naragund, Ruxanabi; Singh, Y V; Bana, R S; Choudhary, A K; Jaiswal, Pranita (The Indian Journal of Agricultural Sciences, 2020)
It was concluded that zero tillage with 2.5 t/ha residue of chickpea crop and combined inoculation of Rhizobium + PSB + AM Fungi gave higher productivity and profitability as well as enhanced macro and micro nutrients in grain and stover of summer greengram over the other methods of crop establishment, viz. conventional and zero tillage without microbial inoculation. Thus farmers may inoculate with combination of Rhizobium+ PSB + AM Fungi in summer greengram and sow the crop through zero tillage with 2.5 t/ ha crop residue to get higher productivity, profitability and nutrient concentration in grain.